The other Boleyn girl [videorecording (DVD)] - Chadwick, Justin; Portman, Natalie, 1981-; Johansson, Scarlett, 1984-; Bana, Eric; Gregory, Philippa (Sony Pictures Home Entertainment, 2008)
Anne Boleyn is a doe-eyed vixen who is ordered by her power-hungry uncle to bewitch King Henry VIII. Her shy sister Mary has always been in Anne's shadow. Anne is prettier, more accomplished, and desired by many men. So when the King picks Mary as his mistress, Anne turns on her sister and schemes to become not only the King's consort, but his new queen. Though the Boleyn girls' mother points out that her 'daughters are being traded like cattle for the advancement of men,' it is Anne who ultimately throws her slight weight around to bully Henry into doing her bidding.